THE TUMOR IMMUNE MICROENVIRONMENT AS A KEY DETERMINANT OF DISEASE PROGRESSION AND THERAPEUTIC RESPONSE IN HPV-ASSOCIATED CERVICAL CANCER (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This thesis synthesizes current concepts of HPV-driven immune remodeling across disease stages, highlights TIME features associated with progression and outcome, and discusses actionable translational strategies—including biomarker-guided immunotherapy combinations, microenvironment reprogramming, and multi-omics profiling—to improve responses and durability of control.